Feasibility Study on the Spread of NZEBs Using Economic Incentives - Diana D’Agostino; Milena Esposito; Francesco Minichiello; Carlo Renno (Energies, 2021)
Nowadays, environmental and energy issues attract a lot of attention in the civil buildings sector, leading to the emergence of new technologies and new targets, which include Net Zero Energy Buildings (NZEBs). However, despite the great response in scientific research, the spread of NZEBs in Europe is quite limited. This is due not only to the lack of transposition of the related European Directives into the various national legislations, but also to the high initial cost of such high-performance buildings. The aim of this paper is to demonstrate how different energy retrofit strategies on existing buildings can lead to the achievement of the NZEB target if encouraged by tax incentives, at zero or almost zero cost. The introduction of tax incentives by individual EU member states would allow the spread of NZEBs that are still underdeveloped, especially in highly urbanized contexts. A suitable building energy dynamic simulation software has been used. The case study refers to a villa located in Southern Italy and for which different energy retrofit strategies are proposed to reach the NZEB target. For each case, an energy and economic evaluation is carried out to evaluate the feasibility of the interventions, exploiting the so-called “Super-Eco-Bonus 110%” incentive. The main results highlight that among the various solutions, the greatest energy cost reductions are obtained with the use of heat pump generators. Furthermore, the solution with the biomass boiler allows the use of a smaller number of photovoltaic panels to meet the yearly energy balance of the NZEB.